Terrorist rehabilitation a new frontier in counter-terrorism - Gunaratna, Rohan; Bin Ali, Mohamed (Imperial College Press insurgency and terrorism series, 2015)
With the rise of religiously motivated violence and terrorism, governments around the world need to develop their religious and ideological capabilities in parallel with strengthening their law enforcement, military and intelligence capabilities.